Real-time and recollected ratings of pain, mood, and fatigue in older adults - Rachel L. M. Ho; Trey B. Warren; Jinhan Park; Young Seon Shin; Matthew Petersen; Yenisel Cruz-Almeida; Stephen A. Coombes (PAIN Reports)
Abstract. Introduction:. Pain intensity variability refers to the fluctuations in pain intensity levels experienced by an individual over time. Technological advances have simplified the use of ecological momentary assessment (EMA) paradigms for researchers and participants allowing for easier measurement of pain intensity variability by measuring pain intensity multiple times a day over several days. In this study, we used EMA to investigate the relationship between variability in pain intensity, mood, and fatigue and accuracy of recall in older adults. Methods:. Twenty-six cognitively normal participants aged 60 and above completed EMA 3 times daily over 14 days, rating their pain intensity, mood, and fatigue using a smartphone application. On the 15th day, participants were asked to recall their average levels of these variables. Results:. We found that greater variability in pain intensity was significantly associated with poorer recall accuracy, even when controlling for peak pain, end pain, and the number of painful areas. However, no significant associations were found between variability and recall accuracy for mood or fatigue. Conclusion:. These results suggest that the difficulties with recall accuracy are specific to pain intensity and do not extend to mood or fatigue, highlighting the importance of considering pain intensity variability in understanding and managing pain in older adults.